Developing a Dictionary Model for Balinese Speech Levels: A Study Based on Classification Principles and Semantic Feature Analysis - Arnawa, Nengah; Ngurah Sulibra, I Ketut; Suardiana, I Wayan (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This study aimed to develop a model for addressing multiple identities of the Balinese lexicon within the anggah-ungguhing (speech level) system. The model developed is expected to resolve the multiple identities frequently found in the Balinese speech level dictionaries and similar references. Furthermore, this study was based on the principles of classification, applying the theory of lexical semantic feature differentiation. A qualitative method was used, and the data were collected through document recording and questionnaire methods. The data were then analyzed using the extralingual context method, with a focus on the domain of lexical use. This process facilitated the creation of a matrix for the Balinese lexical semantic differentiation and a work table for vocabulary identification within the speech level system. The two conceptual products effectively addressed the multiple identities of the Balinese words within the speech level system.
Keywords: speech levels; dictionary development model; multiple identities of the Balinese lexicon; a matrix of the Balinese lexical semantic differentiation